Analisis faktor-faktor yang mempengaruhi Price Earnings Ratio (PER) perusahaan pertambangan di bursa efek indonesia - sonny fransisco siboro (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2019)
One of the fundamental analysis that usually used by investor and security analyze to value the stock price by Price Earnings Ratio (PER) approach. Price Earnings Ratio shows how much investor is willing to pay per rupiah of companies’ profit. These researches have as a purpose to examine influence factor of Dividend Payout Ratio (PER),  Return On Equity (ROA), Earnings Per Share (EPS), Leverage, Size to Price Earnings Ratio (PER).